Investigation of Growth Performance, Proximate and Fatty Acid Composition of Freshwater (Euglena gracilis, Chlorella vulgaris) and Marine (Pavlova lutheri, Diacronema vlkanium) Microalgae - Kamil Mert Eryalçın; Merve Sayar (Aquatic Sciences and Engineering)
This work is focused on investigating the nutrient compositions, growth, and fatty acid composition of Chlorella vulgaris, Euglena gracilis, Pavlova lutheri, and Diacronema vlkanium, which are natural diets of bivalve, crustaceans, live prey such as rotifer, copepods, daphnia and feed ingredients in aquaculture nutrition. Microalgae culture was performed in a live feed laboratory under controlled physical and chemical conditions. The initial concentration of microalgae species was adjusted as 2×106 cells/mL and growth performance was calculated by Neubauer Hemocytometer daily. The maximum growth performance was detected in Diacronema vlkanium culture with 1.78×107 cells/mL. In the case of proximate composition, the highest dry matter content was found in Pavlova lutheri (6.21%). Freshwater microalgae species Chlorella vulgaris (50.5%) and Euglena gracilis (42.5%) had high crude protein compared to Pavlova lutheri and Diacronema vlkanium. Fatty acid compositions of microalgae were also determined. The highest EPA (C20:5n-3) content was found in Pavlova lutheri (6.85%) whereas arachidonic acid (C20:4n-6) and docosahexaenoic acid (C22:6n-3) contents were only found with a level of (3.32%) and (1.79%) in Euglena gracilis, respectively. Microalgal culture should have high biomass in a short time of culture and in this study, E.gracilis and P.lutheri showed high growth and essential nutrients gain in laboratory scale production and this result could be applied in larger volume photobioreactor.